THE SOCIAL DIMENSION OF COASTAL EROSION: THE CASES OF ESPINHO/PARAMOS AND FONTE DA TELHA - Duarte de Almeida, I. (11th International Conference on Intercultural Mediation and Social Intervention – “Territories, Municipalities, Networks, and Partnerships: Intercultural Mediation and Social Intervention, 2024)
This work examines society's perception of coastal erosion and its risks. As activities in coastal areas have increased and diversified, ecosystems have been damaged, and erosion along the coast has increased. Inland communities tend not to perceive erosion risks and rely on government-financed engineering structures to protect themselves. Environmental, economic, and social variables play a role in this. This complexity can lead to conflicts, resource disputes, negative impacts, and scepticism towards coastal management strategies. Public participation is critical to managing coastline risks sustainably. This paper addresses coastal erosion's social-economic and environmental effects in a Portuguese coastal urban area.